2008
DOI: 10.1185/030079908x260871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo biloba extract on lopinavir, midazolam and fexofenadine pharmacokinetics in healthy subjects

Abstract: Objective: Animal and in vitro data suggest that Ginkgo biloba extract (GBE) may modulate CYP3A4 activity. As such, GBE may alter the exposure of HIV protease inhibitors metabolized by CYP3A4. It is also possible that GBE could alter protease inhibitor pharmacokinetics (PK) secondary to modulation of P-glycoprotein (P-gp). The primary objective of the study was to evaluate the effect of GBE on the exposure of lopinavir in healthy volunteers administered lopinavir/ritonavir. Secondary objectives were to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 23 publications
2
69
0
2
Order By: Relevance
“…A study investigated the influence of Ginkgo biloba extract on the pharmacokinetics of fexofenadine [31]. After an intake of Ginkgo biloba extract (120 mg bid) for two weeks a non significant reduction by 20 % in fexofenadine AUC was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigated the influence of Ginkgo biloba extract on the pharmacokinetics of fexofenadine [31]. After an intake of Ginkgo biloba extract (120 mg bid) for two weeks a non significant reduction by 20 % in fexofenadine AUC was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike competitive enzyme inhibition, enzyme induction by G. biloba is a slow regulatory process because new protein must be synthesized. A 14-day pretreatment was chosen on the basis of previous in vivo studies [20][21][22] and to prevent unnecessarily long exposure of healthy volunteers to G. biloba.…”
Section: Discussionmentioning
confidence: 99%
“…Although ginkgo biloba extract has potential beneficial effects, self-medication with ginkgo biloba may lead to undesirable drug interactions with regular medication. For example, a study in healthy subjects showed that plasma concentrations of midazolam (a CYP3A probe) were significantly reduced after ginkgo biloba intake (22). If this were also true with antiretroviral agents, it could place individual patients at risk for virological failure.…”
mentioning
confidence: 99%